2011
DOI: 10.1590/s0365-05962011000600012
|View full text |Cite
|
Sign up to set email alerts
|

Combining diagnostic procedures for the management of leishmaniasis in areas with high prevalence of Leishmania guyanensis

Abstract: BACKGROUND: The Amazon region corresponds to approximately 40% of the cases of leishmaniasis in Brazil. We report a prospective study with 180 patients conducted in a health care unit that diagnoses 10% of the cases of leishmaniasis in the Brazilian Amazon. The study addresses how a combination of procedures improves diagnosis in areas with high prevalence of Leishmania guyanensis. OBJECTIVES: to evaluate diagnostic methods in areas with high prevalence of Leishmania guyanensis. METHODS: All subjects were amas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 12 publications
0
7
0
1
Order By: Relevance
“…More recently, trials with miltefosine performed at FMT-HVD demonstrated that this compound had an effi cacy of 71.4% in the treatment of L. (V.) guyanensis (27) . The implementation of new diagnostic tests, such as polymerase chain reaction (PCR), for ATL diagnosis at FMT-HVD has created the opportunity for this reference unit to enhance their role in the species-specifi c detection of the parasite and to improve the current knowledge about the disease behavior in the region (28) .…”
Section: Clinical Characteristics Diagnosis and Treatmentmentioning
confidence: 99%
“…More recently, trials with miltefosine performed at FMT-HVD demonstrated that this compound had an effi cacy of 71.4% in the treatment of L. (V.) guyanensis (27) . The implementation of new diagnostic tests, such as polymerase chain reaction (PCR), for ATL diagnosis at FMT-HVD has created the opportunity for this reference unit to enhance their role in the species-specifi c detection of the parasite and to improve the current knowledge about the disease behavior in the region (28) .…”
Section: Clinical Characteristics Diagnosis and Treatmentmentioning
confidence: 99%
“…In the Amazonas, L . guyanensis is the main etiological agent of ATL [ 3 ]. Classical forms of ATL (cutaneous, disseminated, diffuse and mucosal leishmaniasis) are caused by L .…”
Section: Introductionmentioning
confidence: 99%
“…guyanensis . [ 2 ]. Another limitation is the non-blind evaluation by the medical staff, which may cause a bias in the recording of data.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of vectors and infection in peri-urban zones, that were not previously endemic areas, are emerging. [ 1 , 2 ]…”
Section: Introductionmentioning
confidence: 99%